2004
DOI: 10.4049/jimmunol.173.12.7647
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Activation by Antibody-Like Immunoreceptors: Increase in Affinity of the Single-Chain Fragment Domain above Threshold Does Not Increase T Cell Activation against Antigen-Positive Target Cells but Decreases Selectivity

Abstract: Chimeric TCRs with an Ab-derived binding domain confer predefined specificity and MHC-independent target binding to T cells for use in adoptive immunotherapy. We investigated the impact of receptor binding affinity on the activation of grafted T cells. A series of anti-ErbB2 single-chain fragment binding domains with a Kd ranging from 3.2 × 10−7 to 1.5 × 10−11 M was linked to CD3ζ-derived immunoreceptors and expressed in human PBL. Solid phase bound ErbB2 protein triggered activation of receptor-grafted T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
234
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(257 citation statements)
references
References 21 publications
17
234
2
4
Order By: Relevance
“…EGFR expression has been observed in both epithelium-derived malignancies and most epithelial cells, raising great concerns in the target-mediated toxicity on EGFR-expressing normal tissues. However, the lower affinity of CAR molecule with EGFR antigen may discriminate the damage activities between normal cells with relatively lower level expression of EGFR and tumors with higher expression (Caruso et al, 2015;Chmielewski et al, 2014;Liu et al, 2015). In this study, tolerable and controllable EGFR targeting-related toxicities were just observed in 11 NSCLC cases as shown in Table 2, implying an appropriate affinity of EGFR-CAR epitope we adopted.…”
Section: Discussionmentioning
confidence: 77%
“…EGFR expression has been observed in both epithelium-derived malignancies and most epithelial cells, raising great concerns in the target-mediated toxicity on EGFR-expressing normal tissues. However, the lower affinity of CAR molecule with EGFR antigen may discriminate the damage activities between normal cells with relatively lower level expression of EGFR and tumors with higher expression (Caruso et al, 2015;Chmielewski et al, 2014;Liu et al, 2015). In this study, tolerable and controllable EGFR targeting-related toxicities were just observed in 11 NSCLC cases as shown in Table 2, implying an appropriate affinity of EGFR-CAR epitope we adopted.…”
Section: Discussionmentioning
confidence: 77%
“…21 To generate the retroviral expression cassettes for the anti-ErbB2-scFv-Fc-CD28-CD3z CARs with combined CD28-CD3z signalling domain, the C6.5 scFv DNA and its derivatives (kindly provided by Dr J Marks, UCSF) ( Table 1) were amplified by PCR using the following set of primer oligonucleotides (NcoI and BamHI restriction sites are underlined): 5¢-CGTACCATGGATTTTGANTIGENGT GCANTIGENATTTTCANTIGENCTTCCTGCTAATCANTIGENTGCCTCAGT CATAATGTCTANTIGENACCGGCGATGGCCCANTIGENGTG-3¢ (sense) and 5¢-TTCTGGATCCGCACCTANTIGENGACGGTGACCTT-3¢ (antisense). The amplified anti-ErbB2 scFv DNA replaced the scFv DNA of the BW431/ 26scFv-Fc-CD28-CD3z CAR, which was previously described.…”
Section: Generation Of Recombinant Carsmentioning
confidence: 99%
“…The amplified PCR product CD8-CD3z was excised with BamHI and XhoI and cloned between the BamHI and XhoI sites of the anti-ErbB2 CAR encoding vectors. 21 T cells were transduced with recombinant retroviruses as described in detail elsewhere. 35 Cells were analyzed by flow cytometry.…”
Section: Generation Of Recombinant Carsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the antigen was immobilised on a solid surface CAR-mediated T-cell activation was reported to be dependent on the strength of the interaction, because of the correlation between the affinity of different CAR T-cellconstructs and IFN-release by the CAR T-cells [20] .…”
Section: Affinity Of Car T-cellsmentioning
confidence: 99%